2010
DOI: 10.15809/irriga.2010v15n3p301
|View full text |Cite
|
Sign up to set email alerts
|

Tolerância Do Pepino À Salinidade Em Ambiente Protegido: Efeitos Sobre Propriedades Físico-Químicas Dos Frutos

Abstract: A salinidade provocada pelo mau uso da fertirrigação pode causar muitos danos às plantas e consequentemente à produção. Este trabalho teve como objetivo avaliar os frutos da cultura do pepino, em relação aos parâmetros pH, sólidos solúveis totais (%), acidez total titulável (g 100g-1 de amostra) e firmeza de polpa (kgf), cultivada em meio salino. Os tratamentos foram compostos pelos seguintes fatores: dois tipos de manejo de fertirrigação (M1 e M2) e seis níveis iniciais de salinidade do solo (S1=1,5; S2=2,5; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
4
0
7
Order By: Relevance
“…Similarly, Eloi et al (2011) and Medeiros (2010) found no difference in the pH of the fruit pulp when a tomato crop was grown in a greenhouse, employing the same fertigation managements (M 1 and M 3 ) used in this work. A fact also reported by Medeiros et al (2010) in a cucumber crop.…”
Section: Level Of Nk (%) Management -------------------------------Vasupporting
confidence: 72%
See 2 more Smart Citations
“…Similarly, Eloi et al (2011) and Medeiros (2010) found no difference in the pH of the fruit pulp when a tomato crop was grown in a greenhouse, employing the same fertigation managements (M 1 and M 3 ) used in this work. A fact also reported by Medeiros et al (2010) in a cucumber crop.…”
Section: Level Of Nk (%) Management -------------------------------Vasupporting
confidence: 72%
“…Tavares (2005), working with a pepper crop in a greenhouse, but using a substrate of coconut fibre, saw no response from the pepper crop to N and K levels for pH, SS and TA. However, Medeiros et al (2010), working with a cucumber crop, found an increasing linear response for TA to increased concentrations of salt in the soil. Macedo and Alvarenga (2005) observed an increase in TA in response to potassium levels in tomatoes.…”
Section: Level Of Nk (%) Management -------------------------------Vamentioning
confidence: 97%
See 1 more Smart Citation
“…For the variable soluble solids, Dias et al (2011) reported negative effects in the pulp of yellow passion fruits as a function of irrigation water salinity, while Medeiros et al (2010) observed positive effect for the pulp of cucumber fruits as a function of soil salinity.…”
Section: Resultsmentioning
confidence: 99%
“…Em quanto que Medeiros et al(2011) trabalhando com melão amarelo híbrido Mandacarú observou influência da salinidade na água de irrigação para essa variável. Em outro estudo, Medeiros et al(2010) trabalhando com pepino em ambiente protegido observou que o aumento da salinidade do solo tende a diminuir a firmeza da polpa desses frutos.…”
Section: Materiais E Métodosunclassified